Nitroxide Amide-Bodipy Probe Behavior in Fibroblasts Analyzed by Advanced Fluorescence Microscopy - Aspee-Lamas, A (Royal Society of Chemistry, 2016)
A novel synthesized nitroxide amide-BODIPY prefluorescent probe was used to study cellular redox balance that modulates nitroxide/hydroxylamine ratio in cultured human fibroblasts. FLIM quantitatively differentiated between nitroxide states of the cytoplasm-localized probe imaged by TIRF, monitoring nitroxide depletion by hydrogen peroxide; eluding incorrect interpretation if only fluorescence intensity is considered. © 2016 The Royal Society of Chemistry.